Criminal Law Regulation of Online Non-contact Indecent Acts: Taking the Case of Li's Forced Indecent Assault as an Example - Zhang, Bohan (International Journal of Social Sciences and Public Administration, 2025)
In the digital era, where the Internet is deeply integrated into social life, the frequent occurrence of online indecent assault cases poses significant harm to the physical and mental health of minors. While it is practically necessary to regulate online indecent assault through criminal law, merely relying on practical necessity is insufficient to justify the rationality and legitimacy of convicting and punishing such acts under the crime of compulsory indecent assault. In-depth legal analysis is still required. The term "indecent assault" carries strong moral evaluations and normative connotations. By analyzing its core semantics and categorizing relevant behaviors, it can be concluded that online nude chatting falls within the semantic scope of "indecent assault." Although inveiglement is prevalent in online indecent assault cases, it does not meet the requirement of "coercion" and thus cannot violate the principle of legality for the sole purpose of "protection." Compared with offline indecent assault, online indecent assault poses less risk of physical violence but a higher risk of privacy dissemination. Therefore, judgment of the degree of criminality should be made in consideration of its particularities.